2017
DOI: 10.1017/ice.2016.316
|View full text |Cite
|
Sign up to set email alerts
|

Paramyxovirus Outbreak in a Long-Term Care Facility: The Challenges of Implementing Infection Control Practices in a Congregate Setting

Abstract: objective. We report an outbreak of respiratory syncytial virus (RSV) and human metapneumovirus (HMPV) infections in a dementia care ward containing 2 separately locked units (A and B) to heighten awareness of these pathogens in the older adult population and highlight some of the infection prevention challenges faced during a noninfluenza respiratory viral outbreak in a congregate setting.methods. Cases were defined by the presence of new signs or symptoms that included (1) a single oral temperature ≥ 37.8°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…A poor sensitivity or specificity of an assay results in either inaccurate diagnoses or a lack of confidence in results. High assay costs make certain laboratory tests unfeasible and shift the financial burden to other aspects of clinical care, such as the decision to risk a potential outbreak or to isolate patients merely as a precaution (15). …”
Section: Discussionmentioning
confidence: 99%
“…A poor sensitivity or specificity of an assay results in either inaccurate diagnoses or a lack of confidence in results. High assay costs make certain laboratory tests unfeasible and shift the financial burden to other aspects of clinical care, such as the decision to risk a potential outbreak or to isolate patients merely as a precaution (15). …”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the outbreaks are presented in Tables 2-4. Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
“…In 8 studies, it was not possible to calculate the rate due to lack of information. The highest attack rate of 73.17% was reported in an outbreak of respiratory syncytial virus (RSV) and human metapneumovirus (HMPV) [50], followed by Clostridium difficile (51.97%) [27] and viral gastroenteritis caused by norovirus and rotavirus (48.6%) [26]. Influenza-like illness had the median overall attack rate of 24.50%.…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, illness may also occur in staff members. Challenges may arise because these environments are not thought of as primary health care environments and may not have infection control protocols that are as stringent as those in health care settings (23,24).…”
Section: Epidemiology and Clinical Presentation Of Acute Respiratory mentioning
confidence: 99%